Pendidikan Karakter Nilai Disiplin dan Tanggung Jawab dalam Pembelajaran Tematik di Sekolah Dasar - Raudho Zaini (Journal Innovation In Education, 2025)
Teachers now have a responsibility to help their students develop an understanding of character values ​​as part of the educational process. However, increasing attention to character values ​​does not seem to be an integrated component of ongoing teaching. The purpose of this study was to analyze the importance of characters such as discipline and responsibility in subject education. This study used a qualitative descriptive methodology. While the subjects used were teachers and grade III students in the SDN system. The method of collecting information through observation, interviews, and questionnaires. This research method uses observation notes, interviews, and questionnaires. Data reduction, analysis, and interpretation are three phases of descriptive data analysis. The results of the study showed that the value of discipline as measured by the indicator of compliance with school regulations was quite high. Meanwhile, you are very good at taking responsibility for your actions. Character and value education is very important during the learning process because it has a direct impact on student actions both inside and outside the classroom.